APLIKASI TEKNOLOGI FERMENTASI LIMBAH SAGU UNTUK MENUNJANG KETERSEDIAAN PAKAN SAPI DI DESA PUPUAN TEGALLALANG GIANYAR BALI - N.G.K. Roni; T.B. Kusmiyarti; N.W. Siti; N.K. Karyati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Community service activities that aim to transferring fermentation technology to make silage feed to supportof breeding Balinese cattle in Pupuan Village, Tegallalang District, Gianyar Regency. The methods appliedin the community empowerment are as follows: (1) Participatory coordination and communication withlivestock breeding groups to formulate programs planning, operation and evaluation; (2) Counseling to buildcommunity perceptions and understanding of innovations or programs implemented; (3) Training andsimulation of applied ipeks transferred to the community; (4) Assistance is regular and continuous meetingsbetween assistants with target communities to transferred science and technology can be implementedindependently by the community. The results show that dissemination activities through IbW program inPupuan Village, Tegallalang district, Gianyar Regency can take place well indicated by active participationand high adoption of science and technology. The active participation of partners in all technologicaldissemination activities is quite high, ie the presence of group members at the time of counseling and trainingreaches 100%, who ask/express opinion 60%, and try to practice 68%. The ability of science and technologyadoption and partner initiatives to produce products independently is high enough, at 60%